ABC method in sweets production by a brazilian women association (Costos y Gestión, 2023)
Associations are non-profit organizations with the purpose of defending collective interests, developing economic activities and impacting and transforming people's lives. However, they present management difficulties, especially with respect to costs, because their accounting practice is still underdeveloped. A costing tool is essential in any type of organization and, in this context, this work sought, through quantitative research and through the Activity-Based Costing method, to measure the management costs of a women's association that works in the handcraft production of coconut sweets. The case study was developed in an association, located in the city of Lucena- PB-BR, which manufactures two types of coconut sweets: traditional and cut. Data collection was carried out using observation, document analysis and interviews. The results showed that the association needs to formalize its Production Planning and Control, in order to produce more efficiently. Fifty-two micro-activities were identified, 77% of which were considered to add value to products. The analysis of the management cost of the production showed that traditional sweets generate profits, while cut sweets imply a loss for the association.
Keywords: activities; costs; management; processes